2018
DOI: 10.1002/sdtp.12359
|View full text |Cite
|
Sign up to set email alerts
|

58‐3: Sub‐KHz 4000‐PPI LCoS Phase Modulator for Holographic Displays

Abstract: A 4,000 PPI phase-only NCTU PCU-3-01 LCoS-SLM filled with UCF-L1 NLC was assembled and evaluated. The resulting LCoS panel possessed 1.6 ms of linear-full-phasemodulation response time under digital driving (V w = 4.5 V, V b = 0.3 V) at T = 45 o C. The 3D holographic images show that most diffracted light is transferred within 2 ms. Meanwhile, a low-latency driver solution based on 1920 x 640 at 240Hz (equivalent to 4000 PPI) input frame rate and 720 Hz data frame rate were presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…High pixel density (~7000 ppi) 4K2K LCoS IC backplane suffers from low driving voltage (<3.3 V) limitations. The recently reported fast response time LCoS with PCM-2-01, L1, MCRI or UCF-L1 also requires at least 4~6 V driving voltage [22][23][24][25][26]. In this paper, we revealed a novel 1.2-inch 4K2K TN amplitude-type LCoS microdisplay (PCU-3-02-MD) with 1-ms RT under 5.0 V for displays.…”
Section: Introductionmentioning
confidence: 84%
“…High pixel density (~7000 ppi) 4K2K LCoS IC backplane suffers from low driving voltage (<3.3 V) limitations. The recently reported fast response time LCoS with PCM-2-01, L1, MCRI or UCF-L1 also requires at least 4~6 V driving voltage [22][23][24][25][26]. In this paper, we revealed a novel 1.2-inch 4K2K TN amplitude-type LCoS microdisplay (PCU-3-02-MD) with 1-ms RT under 5.0 V for displays.…”
Section: Introductionmentioning
confidence: 84%
“…w pixel and w fb are illustrated in Figure 7b, where it can be seen that both, being finite sizes, reduce the quality of the refractive index profile. The smallest pixel sizes currently achieved when the device is placed upon a silicon backplane (Liquid Crystal on Silicon, LCoS), are around 5 µm [104,108]. Due to silicon's high reflectivity, such LCoS devices can only operate in reflection mode, whereas Liquid Crystal on Poly Silicon (LCoPS) can work in transmission mode leads to larger minimum pixel sizes [21,109].…”
Section: Electronically Addressed Refractive Spatial Light Modulatorsmentioning
confidence: 99%
“…Several approaches to achieve high frame rates in high-resolution panels (≥4000 ppi) have been realized recently. Yang et al demonstrated 4000 ppi in a 0.55-inch 1920 × 1080 IC backplane with a pixel pitch of approximately 6.4 μm [23]. Abeeluck et al demonstrated a digital drive LCoS micro-display with a pixel pitch of 3 μm and a high fill factor of 93.5% in resolutions from 1080p to 4K [24].…”
Section: High Resolution and High Pixel-per-inch (Ppi)mentioning
confidence: 99%